Study of heavy metal levels in seawater in the vicinity of Single Buoy Moorings at Mina Al Fahal, Sultanate of Oman - Abdul-Wahab, Sabah Ahmed; Al-Husaini, Issa; Ahamad, Rahmalan; Yetilmezsoy, Kaan; Abdo, Jamil (TAYLOR & FRANCIS LTD, 2016)
This study was conducted to determine the concentrations of cadmium, copper, lead, and vanadium in seawater samples taken from the vicinity of Single Buoy Mooring 3 (SBM3) at Mina Al Fahal in the Sultanate of Oman. SBM3 is one of three locations at Mina Al Fahal (SBM1 and SBM2) associated with importing and exporting refined petroleum products. Using graphite furnace atomic absorption spectrophotometry, concentrations of these four metals in seawater samples were measured in six samples. None of the metals was present in concentrations greater than the European Commission/United Kingdom Environmental Quality Standards, but a comparison to previous data collected at SBM2 indicates that concentrations have increased approximately 40% over the past two decades. To better identify sources of the metals, it is imperative to monitor effluents and collect more targeted samples at and/or near discharge points.
Keywords: Heavy metals; marine ecology; pollution monitoring; seawater; single buoy moorings; ARABIAN GULF; SAUDI-ARABIA; POLLUTION; FISH; SEDIMENTS; WAR; Environmental Sciences & Ecology